The Criminalization of Border Solidarity and the Law as a Double-Edged Weapon - Trucco, Daniela (PARTECIPAZIONE E CONFLITTO, 2023)
Criminalization of solidarity towards migrants at the external and internal borders of Europe is in full swing. It roots into the wider process of criminalisation of racialised foreigners and their mobility towards and within Europe, as well as into the increasing judicialization of direct activism and grassroots social movements on the ground of anti-terrorism. Law and society scholarship has grasped the complex relationship between legal institutions or tools and social movements, and how these latter can use Law as an offensive or defensive weapon to protect themselves and enhance their cause. Activists can also turn the weapon of Law against the State, when using repressive measures and trials as mediatic and political stages to launch general statements and denounce the State’s inconsistency and law violations. Aiming at contributing to the understanding of the room and conditions to transform judicialization into a political weapon, the article investigates a peculiar case of criminalization of solidarity, namely the territorial bans issued by Italian police against "No Border" activists on the French-Italian border of Ventimiglia since 2015. It points out that, in spite of the annulment of the bans obtained by the defendants and their lawyers in court, the peculiar features of the repressive tool, of the social movement itself and of the context in which they occurred, strongly limited the possibility of a political reversal of judicialization. Crossing a legal opportunities framework with a legal consciousness perspective, the article also shows the plurality of activists’ attitudes towards law and the effects of criminalization on activists’ life paths.